Concussion in pediatric surgical patients scheduled for time-sensitive surgical procedures. (May 2017) - Ferrari, Lynne R; O'Brien, Michael J; Taylor, Alex M; Matheney, Travis H; Zurakowski, David; Slogic, Katherine; Anderson, Michelle; Soriano, Sulpicio; Rockoff, Mark; Tasker, Robert C
Background: Each year in the United States approximately three million individuals sustain sport or recreation-related concussion which may occur in the setting of orthopedic trauma requiring surgical intervention under general anesthesia. The effects of surgery and general anesthesia on brain recovery are currently unknown. The objective of this study was to determine the prevalence of recent sport concussion, recognized or not, in a preoperative, pediatric, surgical population. Methods: The study involved administering a questionnaire to all eligible, consented patients in one of the following settings: Preoperative Clinic, Day Surgery Unit, Trauma Clinic, or inpatient floor. The questionnaire was designed to determine the occurrence and symptoms of a concussion. This study was conducted at an urban 395-bed comprehensive center for pediatric health, between May 2014 and April 2015. Inclusion criteria for study were age 5–21 years, presentation for surgical repair of orthopedic traumatic injury or nasal fracture, and precipitating injurious event occurring within four weeks of surgery. Results: The prevalence of concussion in the setting of orthopedic trauma, either known or unknown at the time of presentation for surgery was 6%. The interval between surgery and injury was between three and 13 days. Prior education for recognition of concussion was present in 66% of patients. Conclusions: The impact of surgery with general anesthesia in pediatric patients with a recent concussion is unknown. No changes in post-op disposition were noted in this patient population. However, our findings support the need to measure neurocognitive function before and after administration of operative procedures in a larger population with a recent concussion compared with controls.